Cognition and Cognitive Reserve in Cochlear Implant Recipients - Völter, Christiane; Götze, Lisa; Bajewski, Marcel; Dazert, Stefan; Thomas, Jan Peter (Frontiers in Aging Neuroscience, 2022)
At present, dementia is a hot topic. Hearing loss is considered to be a modifiable risk factor for cognitive decline. The underlying mechanism remains unclear and might be mediated by socioeconomic and psychosocial factors. Cochlear implantation has been shown not only to restore auditory abilities, but also to decrease mental distress and to improve cognitive functions in people with severe hearing impairment. However, the promising results need to be confirmed. In a prospective single-center study, we tested the neurocognitive abilities of a large group of 71 subjects with bilateral severe hearing impairment with a mean age of 66.03 (SD = 9.15) preoperatively and 6, 12, and 24 months after cochlear implantation using a comprehensive non-auditory computer-based test battery, and we also assessed the cognitive reserve (CR) [Cognitive Reserve Index (CRI)], health-related quality of life (QoL) (Nijmegen Cochlear Implant Questionnaire), and depression (Geriatric Depression Scale-15). Cognitive functions significantly increased after 6 months in attention (p = 0.00004), working memory (operation span task; p = 0.002), and inhibition (p = 0.0002); and after 12 months in recall (p = 0.003) and verbal fluency (p = 0.0048), and remained stable up to 24 months (p ≥ 0.06). The CR positively correlated with cognitive functions pre- and post-operatively (both p < 0.005), but postoperative improvement in cognition was better in subjects with poor CR (p = 0.003). Depression had only a slight influence on one subtest. No correlation was found among cognitive skills, quality of life, and speech perception (each p ≥ 0.05). Cochlear implantation creates an enriched environment stimulating the plasticity of the brain with a global positive impact on neurocognitive functions, especially in subjects with poor preoperative cognitive performance and low cognitive reserve.